2021
DOI: 10.1144/jgs2021-066
|View full text |Cite
|
Sign up to set email alerts
|

New onshore insights into the role of structural inheritance during Mesozoic opening of the Inner Moray Firth Basin, Scotland

Abstract: The Inner Moray Firth Basin (IMFB) forms the western arm of the North Sea trilete rift system that initiated mainly during the Late Jurassic-Early Cretaceous with the widespread development of major NE-SW-trending dip-slip growth faults. The IMFB is superimposed over the southern part of the older Devonian Orcadian Basin. The potential influence of older rift-related faults on the kinematics of later Mesozoic basin opening has received little attention, partly due to the poor resolution of offshore seismic ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…Although we were unable to recognise any kinematic indicators on these structures, Edwards et al (1993) have described dextral oblique slip on N–S to NNE–SSW trending faults in the Cummingstone area, near the western end of Burghead fault (Figure 2a). Such oblique‐dextral reactivation along NNE–SSW trending faults has also been identified in the Devonian strata in the Turriff sub‐basin (Tamas et al, 2021). U‐Pb calcite dating of syn‐kinematic mineralisation associated with these structures revealed that they likely formed during the Early Cretaceous (130.99 ± 4.6 Ma) under NNW–SSE extension (Tamas et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although we were unable to recognise any kinematic indicators on these structures, Edwards et al (1993) have described dextral oblique slip on N–S to NNE–SSW trending faults in the Cummingstone area, near the western end of Burghead fault (Figure 2a). Such oblique‐dextral reactivation along NNE–SSW trending faults has also been identified in the Devonian strata in the Turriff sub‐basin (Tamas et al, 2021). U‐Pb calcite dating of syn‐kinematic mineralisation associated with these structures revealed that they likely formed during the Early Cretaceous (130.99 ± 4.6 Ma) under NNW–SSE extension (Tamas et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…The Inner Moray Firth Basin (IMFB) is a superimposed rift basin developed on Precambrian to Caledonian metamorphic basement and Devonian–Carboniferous sedimentary rocks related to the older and much larger Orcadian Basin (Figure 1; Tamas et al, 2021 and references therein). From the Permian to the Late Cretaceous, it formed the western part of the intra‐continental North Sea trilete rift system (Andrews et al, 1990; Frostick et al, 1988; McQuillin et al, 1982; Roberts et al, 1990; Thomson & Underhill, 1993; Underhill, 1991).…”
Section: Geological Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies of offshore 3D seismic reflection profiles (e.g., Davies et al, 2001;Long & Imber, 2010;Lăpădat et al, 2016) have argued for a predominance of orthogonal rifting and suggest there is little evidence of oblique-slip faulting in the basin. However, Tamas et al (2021) provide field evidence that strike-slip and obliqueslip faults are recognised in the IMFB basin during basin development, notably along NNE-SSW and NW-SE trends. These faults are thought to represent reactivated Palaeozoic structures related to the earlier Orcadian Basin, which were obliquely reactivated during NW-SE opening of the IMFB.…”
Section: Highlightsmentioning
confidence: 91%
“…Structures from Motion (SfM) and UAV-based SfM have been increasingly used to create 3D outcrop models or Digital Outcrop Models (DOM) and high-resolution Digital Elevation Models (DEM) [ 19 , 20 , 21 ]. UAV photography can be used to create 3D outcrops, as well as aid in mapping, providing images for inaccessible areas, and the creation of orthorectified aerial photographs [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%